Explosive leg strength of elite basketball players - Ademovic, I. H.; Kocic, M. R.; Beric, D. I.; Daskalovski, B. S. (Facta Universitatis: Series Physical Education and Sport, 2015)
The study was performed in order to determine changes in the level of explosive leg strength in elite basketball players after in a 12-week experimental treatment. The study included 15 basketball players from OKK "Konstantin" in Nis in which they are also participants in a basketball league located in Serbia. The youngest basketball player is 18 and the oldest is 26 years old. A sample of measuring instruments consisted tests of explosive leg strength: squat jump, countermovement jump, drop jump and standing long jump. The experimental program lasted for 12 weeks, from January to March 2015 and during this interval there were 36 training sessions, three sessions per week, for the development of explosive leg strength. In addition to training in the experimental treatment, the basketball players had a regular training through a competitive cycle. Statistical analysis included the basic descriptive parameters (mean value - mean and standard deviation - St. Dev) and analysis of variance (MANOVA and ANOVA). Analyses of variance were obtained by changes in the final compared to the initial measurement. The results showed statistically significant changes of explosive leg strength r>0.05. It can be concluded that an experimental treatment significantly affect the date skills.